BS8 Essential role of endothelial ADAR1 RNA editing in vascular integrity. (May 2019) - Tual-Chalot, Simon; Bonini, Francesca; Vlachogiannis, Nikolaos; Doddaballapur, Anuradha; Shook, Kerida; Spyridopoulos, Ioakim; Gatsiou, Aikaterini; Stellos, Konstantinos
Abstract : Introduction: RNA editing is the binding to double-stranded RNA (dsRNA) of the adenosine deaminase acting on RNA (ADAR) family to catalyse the deamination of adenosine (A)-to- inosine (I). We have recently reported that ADAR1 is the main RNA editor in endothelial cells (ECs) and is dysregulated in human atherosclerotic heart disease. However, the role of ADAR1 in the mammalian vascular system has not been reported so far. The goal of the present study is to evaluate the role of EC-restricted ADAR1 in vascular homeostasis in vivo. Methods: Constitutional or inducible EC restricted ADAR1 ablation was achieved by crossing mice carrying a conditional (floxed) ADAR1 allele with either a Tie2-Cre or with a tamoxifen-inducible Cdh5-CreERT2 mouse line. EC function was assessed by the postnatal retinal angiogenesis model, barrier function assays and immunohistochemistry of lung and liver tissues. Cell culture assays, gene-silencing techniques, RT-qPCR, western blot and confocal microscopy were used to assess the ADAR1 effects in intracellular endothelial signalling. Results: The genetic loss of ADAR1 in ECs caused prenatal lethality at embryonic stage E13.5, demonstrating an essential role for endothelial ADAR1 in development. Postnatal ADAR1 ablation resulted in reduced vascular outgrowth, reduced vessel branching in the central vascular plexus and decreased filopodial protrusions from ECs at the angiogenic front of the vascular plexus compared with littermate control mice at P5. Furthermore, endothelial ADAR1 ablation in adult mice resulted in sudden death within 6–8 days after activation of Cre recombinase due to development of severe pleural effusions caused by widespread vascular leakage, indicating a disturbance of EC barrier function in lung microvasculature. Mechanistically, ADAR1-mediated RNA editing is essential for the metabolism of endogenous long-to-short dsRNAs, while silencing of endothelial ADAR1 resulted in accumulation of cytoplasmic long dsRNAs. Long dsRNAs are recognised as a danger-associated molecular pattern by the cytosolic innate immune sensing and signalling sensors. Consequently, the cytoplasmic accumulation of endogenous long dsRNAs resulted in activation of innate immune system in ECs, as assessed by the induction of interferon-β. Concomitantly, activation of the cytoplasmic dsRNA sensors resulted in dissociation of β-catenin from VE-cadherin in EC junctions and endocytosis of VE-cadherin. Conclusion: ADAR1-mediated RNA editing of long dsRNAs is essential for the long-to-short dsRNA metabolism and thus suppression of endogenous innate immune sensing and signalling. EC-restricted ADAR1 ablation results in embryonic lethality, impaired retinal angiogenesis at P5 and sudden death in adult mice due to pleural effusions, which all indicate that ADAR1-mediated RNA editing is indispensable for maintenance of vascular barrier integrity. Conflict of interest: none